2023
DOI: 10.1002/adma.202305586
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Field Induces Better Crystallinity and Abundant Defects at Grain Boundaries to Develop CuS Electromagnetic Wave Absorber

Abstract: Ultrasonic field (USF) is widely used to regulate the intrinsic properties of materials that have not been applied in electromagnetic wave (EMW) absorption. One reason is that the lack of a response mechanism for the materials to USF hinders the expansion of their EMW absorption performance. Therefore, to address this issue, a series of CuS nanoparticles with diverse anions were constructed in the presence or absence of USF. The ultrasonic‐induced cavitation effect can significantly promote CuS crystallization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(6 citation statements)
references
References 65 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…45 Therefore, the existence of semicircles confirms the multi-polarization process, which is beneficial for enhancing the dielectric performance. 46 Furthermore, twisted Cole–Cole semicircles may be observed in all ε ′– ε ′′ curves. This indicates the presence of other polarization relaxation processes, such as Maxwell–Wagner relaxation.…”
Section: Resultsmentioning
confidence: 94%
“…45 Therefore, the existence of semicircles confirms the multi-polarization process, which is beneficial for enhancing the dielectric performance. 46 Furthermore, twisted Cole–Cole semicircles may be observed in all ε ′– ε ′′ curves. This indicates the presence of other polarization relaxation processes, such as Maxwell–Wagner relaxation.…”
Section: Resultsmentioning
confidence: 94%
“…In general, the high shape anisotropy of the magnetic material also contributes to the enhancement of the natural resonance, and thus the magnetic losses of the ball-milled samples S 2 -S 7 were all enhanced relative to the spherical sample S 1 . [55][56][57] The attenuation constants (a) for samples S 1 -S 7 are shown in Fig. 9.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, both the conduction loss and polarization loss contributed to dielectric loss. 58,59 The dielectric parameter diagram indicated that most of the dielectric loss is contributed by the conductive loss and that polarization loss is relatively minor. Both natural resonance and eddy current loss contributed to the magnetic loss.…”
Section: Electromagnetic Wave Absorption Mechanismsmentioning
confidence: 99%